HI 1633 (Pusa Vani): A bio-fortified bread wheat variety for late sown, irrigated conditions of Peninsular Zone of India - Prasad, Sakuru Venkata Sai; Singh, Jang Bahadur; Ambati, Divya; Phuke, Rahul Madho Rao; Prakasha, Thorehalli Linganna; Mishra, Akilesh Nandan; Sharma, Kailash Chandra; Singh, Anil Kumar; Singh, Gyanendra Pratap; Sharma, Jai Bhagwan; Singh, Pradeep Kumar; Yadav, Harikrishna; et al. (Journal of Cereal Research, 2021)
A new bread wheat variety HI 1633 (Pusa Vani) has been released and notified by the Central Sub-Committee on Crop Standards, Notification and Release of Varieties for Agricultural Crops, Government of India for commercial cultivation under irrigated and late sown conditions of Peninsular Zone of India. HI 1633 has average yield of 41.7 q ha-1 and showed superiority over checks. The potential yield of HI 1633 is 65.8 q ha-1 and found resistant to black and brown rusts. HI 1633 found to have excellent chapati quality (7.63), biscuit quality (7.08), high grain hardness (>80.0), test weight (80.3 kg hl-1) and sedimentation value (45.0 ml). It has high protein content (12.4 %) and presence of 5+10 subunit of Glu-D1 reflecting higher gluten strength. It has good amount of micronutrients viz., iron (41.6 ppm) and zinc (41.1 ppm) content making it rich in nutritional qualities. This variety has been recommended for irrigated late sown conditions and would contribute to increasing wheat production and alleviate the socio-economic status of farmers of Peninsular zone in India.